Analisis SWOT Pada Strategi Pemasaran Produk Simpanan Kurban Di KSPPS BMT NU Sejahtera Cabang Jepara - Muyassarah Muyassarah (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2019)
Purpose-The purpose of this research is to introduce the product to the people of Jepara to participate in the "kurban" saving product at BMT NU Sejahtera through SWOT Analysis. Methods-This study uses qualitative methods and applies analytical techniques from various theoretical references and field data to be analyzed and then concludes logically and critically. The data obtained with the approach of observation, interviews, and documentation. Findings-BMT NU who needs to pay attention to strategies to approach customers, networks, and excellent service. BMT NU Jepara also applies the marketing mix or marketing mix/product, price, place, promotion. Implications -Research results can be implemented in all BMT institutions in general and specifically for BMT NU Sejahtera